Pengaruh Profesionalisme Penyidik terhadap Efektivitas Penegakan Hukum dalam Proses Penyidikan Tindak Pidana - Najwa Syabina Aulia; Ayu Nurhaliza Tasimia; Betrilia Betrilia (GLOBAL SCIENTS PUBLISHER, 2025)
The legal issue raised in this study focuses on the low effectiveness of law enforcement in Indonesia, which is often caused by the lack of professionalism among investigators in carrying out criminal investigation duties. This condition results in procedural violations, delays in case handling, and a decline in public trust toward law enforcement officers. The main research question is how the professionalism of investigators influences the effectiveness of law enforcement in the criminal investigation process. The research method used is empirical juridical research with a sociological legal approach, conducted through interviews, observations, and document studies involving police investigators within the jurisdiction of Bengkulu City. The findings indicate that the professionalism of investigators—reflected in their competence, integrity, and adherence to legal procedures—has a significant impact on the effectiveness of law enforcement. Enhancing the quality of human resources, strengthening internal supervision, and providing continuous training are proven to improve the quality of investigations and reinforce public trust in the criminal justice system.